2022
DOI: 10.1186/s40545-022-00490-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics use evaluation among hospitalized adult patients at Jimma Medical Center, southwestern Ethiopia: the way to pave for antimicrobial stewardship

Abstract: Background An irrational antibiotic use is a common problem in developing countries like Ethiopia, which makes empiric antibiotics use difficult. It is considered to be the greatest health problem in our time and future unless intervened. Therefore, this study aimed to assess the patterns of antibiotics use among hospitalized adult patients to pave the way for antimicrobial stewardship. Methods A hospital-based prospective observational study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The role of quality indicators, whether as part of ASPs or separately, is also growing across countries, including African countries, to improve antibiotic prescribing in hospitals, including those based on the AWaRe classification [ 58 , 60 , 64 , 112 , 122 , 123 ]. This is because one way of measuring, monitoring and improving the quality of care is to use indicators, which are standardized measures of healthcare quality that make use of readily available, easy-to-use data independent of subjective judgement.…”
Section: Introductionmentioning
confidence: 99%
“…The role of quality indicators, whether as part of ASPs or separately, is also growing across countries, including African countries, to improve antibiotic prescribing in hospitals, including those based on the AWaRe classification [ 58 , 60 , 64 , 112 , 122 , 123 ]. This is because one way of measuring, monitoring and improving the quality of care is to use indicators, which are standardized measures of healthcare quality that make use of readily available, easy-to-use data independent of subjective judgement.…”
Section: Introductionmentioning
confidence: 99%
“…Also, this route presents a bioavailability of 100%, since the pharmaceutical active ingredient usually reaches the site of action without sufering alterations due to presystemic efects [16][17][18][19]. Tough this route is very efcient, it needs the application of the right dose of the drug due to right prescription, for low or high dose of the drug may lead to many consequences such as antibiotic resistance, low efcacy of the drug, long stay in the hospital, and long treatment leading to high cost and possible high mortality rate [20][21][22]. Te result of our study showed that ceftriaxone was used as empirical treatment in 100% of patients, which is higher than 79.5% in a study performed by Sileshi et al [11], 83.7% in a study conducted by Ayele et al [15], and 82% in a study conducted by Pereira et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…33% (35) (Table 5 and Figure 2). A total of 59.6% (31) indicated that misuse was performed by nurses, and up to 40.4% (21) indicated misuse was performed by medical doctors (Figure 3).…”
Section: Te Misuse Of 3gcmentioning
confidence: 99%
“…It can also serve 11,000 emergency cases and 4500 deliveries per year. It has 800 beds and 1600 staff members (24).…”
Section: Study Design Period and Settingmentioning
confidence: 99%